pH-responsive lyotropic liquid crystals for controlled drug delivery - Negrini, Renata (Langmuir : the ACS journal of surfaces and colloids, 2011)
We present a food-grade lyotropic liquid crystal system, capable of responding to pH variations with a reversible switch in both the structure and physical properties. The system, which is composed by monolinolein and linoleic acid (97:3 wt % ratio) in the presence of excess water at 37 °C and 150 mM ionic strength, is specifically designed to reversibly change from a Im3m reverse bicontinuous cubic phase to a H(II) reverse columnar hexagonal phase, when changing the pH from neutral (pH 7) to acidic (pH 2) conditions, to simulate intestine and stomach conditions, respectively. The pH responsiveness is provided by the linoleic acid, which, being a weak acid (pK(a) ≈ 5), is essentially in the deprotonated charged state at pH 7 and mainly protonated and neutral at pH 2, imposing changes in the critical packing parameter (CPP) of the lyotropic liquid crystal. The use of this system as an efficient controlled-release delivery vehicle is demonstrated on the model hydrophilic drug phloroglucinol, by both release and diffusion studies at different pH, as followed by ultraviolet-visible (UV-vis) spectroscopy. The Im3m cubic phase at pH 7 is shown to release 4 times faster than the H(II) phase at pH 2, making this system an ideal candidate for oral administration of drugs for targeted delivery in intestine or colon tracts